Comparison of differences in immune cells and immune microenvironment among different kinds of oncolytic virus treatments - Wu, Xiaoke (Frontiers in Immunology, 2024)
Oncolytic viruses are either naturally occurring or genetically engineered viruses that can activate immune cells and selectively replicate in and destroy cancer cells without damaging healthy tissues. Oncolytic virus therapy (OVT) represents an emerging treatment approach for cancer. In this review, we outline the properties of oncolytic viruses and then offer an overview of the immune cells and tumor microenvironment (TME) across various OVTs. A thorough understanding of the immunological mechanisms involved in OVTs could lead to the identification of novel and more effective therapeutic targets for cancer treatment.